Geoportal of Costa Rican soils as Public Good at the service of the country - Mata-Chinchilla, Rafael (2019)
Just over 364,000 data on physical, chemical and taxonomic soil characteristics, of 1565 georeferenced sampling points are now accessible through the virtual platform “Geoportal de Suelos de Costa Rica”, at the web address www.suelos.cr. This is an effort led by the Center for Centro de Investigaciones Agronómicas of the Universidad de Costa Rica, together with the Instituto Nacional de Innovación y Transferencia en Tecnología Agropecuaria (INTA), la Asociación Costarricense de la Ciencia del Suelo (ACCS) and the Inter- American Institute of Cooperation for Agriculture (IICA). Although digital soil cartography was started in Costa Rica in the 1990s, successive technological advances and updates in the edaphic taxonomy have forced us to address in an innovative way the organization of a vast amount of information available but dispersed. The work developed has required the design, management and assurance of the quality of two main products, a homogeneous database and geospatial representation through Geographic Information Systems (GIS). Intermediate products of the process have materialized as Protocols for the Management of Information in the Database, a methodological systematization of the process, as well as digital media and multimedia materials (videos) for the use of digital products. The next steps for the Geoportal Platform of Soils of Costa Rica include its dissemination and monitoring of the use by users, the increase in the density and supply of data while maintaining its free access and the possibility of exporting the management model to other countries of the hemisphere.